Cestodes from hector's beaked whale (Mesoplodon hectori) and spectacled porpoise (Phocoena dioptrica) from argentinean waters - Nikolov, Pavel N. (2010)
Single individuals of 2 little-known cetacean species, Mesoplodon hectori and Phocoena dioptrica, stranded and died on the coast of Argentina (Buenos Aires and Chubut provinces, respectively) and were studied for the presence of helminths. The cestodes found were described and illustrated using light microscopy. The following cestode taxa were recovered: Tetrabothrius (Tetrabothrius) hobergi n. sp. (several fragmented specimens, at least 1 gravid) and Tetrabothrius (s.l.) sp. 1 (several fragmented immature specimens) from M. hectori, and Tetrabothrius (s.l.) sp. 2 (single fragmented immature specimen) and 2 morphotypes of tetraphyllidean larvae from P. dioptrica. Tetrabothrius (T.) hobergi n. sp. can be distinguished from Tetrabothrius (T.) forsteri by the greater number of testes and larger eggs and oncospheres, from Tetrabothrius (T.) curilensis by the smaller testes and vitellarium, the shape and size of the ovary, and the larger oncospheres and longer embryonic hooks, and from Tetrabothrius (T.) sp. from Ziphius cavirostris by the narrower strobila, smaller scolex, and smaller number of testes. The generic designations of Tetrabothrius (s.l.) sp. 1 and Tetrabothrius (s.l.) sp. 2 were based on the scolex morphology. Tetrabothrius (s.l.) sp. 1 is closest to Tetrabothrius (T.) forsteri and Tetrabothrius (Biamniculus) innominatus based on the number of testes, while the scolex size of Tetrabothrius (Tetrabothrius) sp. 2 is within the variability range reported for Tetrabothrius (T.) forsteri. More definite identification of the 2 species was not possible due to the condition of the available material. The present study provides the first descriptions of cestodes from M. hectori and P. dioptrica, thus enriching the knowledge regarding the helminths of insufficiently studied marine mammals.